2015
DOI: 10.1016/j.jvs.2015.09.040
|View full text |Cite
|
Sign up to set email alerts
|

First Results of the Covered Endovascular Reconstruction of the Aortic Bifurcation (CERAB) Technique for Aortoiliac Occlusive Disease

Abstract: Objective: Recent studies with asymptomatic carotid patients on best medical management have shown that the annual risk of stroke has decreased to approximately 1%. There is no evidence that a similar decrease in mortality has occurred. In addition, the intensity of statin therapy for these patients has not yet been determined. The aims of this review were to determine (a) the reported long-term all-cause and cardiac-related mortality in patients with asymptomatic carotid stenosis (ACS) >50%, (b) whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…The composite primary end point grouped together the following adverse events (AEs): (1) all death < 30 days and late deaths related to aortic surgery; (2) post-operative hemorrhage necessitating re-operation; (3) myocardial infarction 30 days; (4) any stroke 30 days; (5) postoperative respiratory failure necessitating > 4 days of (24) .37 Female 19 (13) 11 (13) .97 6 (12) 7 (14) .76 BMI ! 30 (Kg/m 2 ) 21 (14) 11 (13) .75 6 (12) 8 (16) .56 COPD 45 (31) 24 (28) .…”
Section: Primary End Pointmentioning
confidence: 99%
“…The composite primary end point grouped together the following adverse events (AEs): (1) all death < 30 days and late deaths related to aortic surgery; (2) post-operative hemorrhage necessitating re-operation; (3) myocardial infarction 30 days; (4) any stroke 30 days; (5) postoperative respiratory failure necessitating > 4 days of (24) .37 Female 19 (13) 11 (13) .97 6 (12) 7 (14) .76 BMI ! 30 (Kg/m 2 ) 21 (14) 11 (13) .75 6 (12) 8 (16) .56 COPD 45 (31) 24 (28) .…”
Section: Primary End Pointmentioning
confidence: 99%
“…But the long term patency rates of endovascular therapies are uncertain for type C and D lesions. (2)(3)(4) In some recent reports authors revealed good results that approximating those of open surgery for type B or C lesions. Saher S Sabri at al.…”
Section: Discussionmentioning
confidence: 98%
“…17 The advantages of the use of covered stents is that it might prevent or immediately treat procedural complications such as rupture and distal embolization, but covered stents are more expensive than bare metal stents, and therefore, the cost-effectiveness of the Covered Endovascular Reconstruction of the Aortic Bifurcation procedure is unclear and long-term data are required. 18…”
Section: Discussionmentioning
confidence: 99%